Management of Islamic Educational Institutions in The Digital Campus Era: Transformation, Risks, And Value-Based Institutional Strategies - Ibnu Alwan; Agung Sholihin (Syntax Corporation Indonesia, 2025)
Digital transformation has become a global phenomenon that fundamentally changes the governance of educational institutions, iluding Islamic educational institutions. The digital campus era requires educational institutions to integrate information technology into management, learning, and academic service systems effectively and sustainably. Although prior research has extensively examined the technological and pedagogical dimensions of educational digitalization, the comprehensive institutional management dimension—particularly how Islamic educational institutions manage the risks, human resource capacity, and value preservation associated with digital transformation—remains underexplored; this gap constitutes the central rationale of the present study. This research aims to analyze the dynamics of the management of Islamic educational institutions in facing digital transformation, especially related to the risk of change, strengthening the capacity of human resources, technological integration, and the preservation of Islamic values in the digital education system. This study uses a qualitative approach with a library research method, examining recent scholarly literature on Islamic education management and education digitalization published between 2019 and 2025. The findings indicate that the success of digital transformation is determined not solely by the availability of technology, but by four interrelated factors: managerial readiness, transformational leadership, organizational culture, and institutions’ capacity to balance technological innovation with spiritual and moral values. Specifically, this study identifies persistent gaps in digital literacy among educators, limited technological infrastructure in regional institutions, and resistance to organizational change as the primary risks confronting digital transformation in Islamic educational institutions. Well-managed digital transformation is shown to improve administrative efficiency, expand access to education, and strengthen the competitiveness of Islamic educational institutions at the national and global levels. This study contributes a conceptual foundation for developing an adaptive, integrative, and value-oriented management model for digital-based Islamic educational institutions, offering both theoretical insight and practical guidance for institutional leaders navigating the digital campus era.